Why Do Manufacturing Facilities Introduce Environmental Management Systems? Improving and/or Signaling Performance - Johnstone, Nick; Labonne, Julien (2012)
In this paper we explore the motivation for the introduction of environmental management systems, and their certification. A distinction is drawn between their role in bringing about better compliance or improved performance, and as external indicators of good environmental practices to both other market participants and regulatory authorities. Drawing upon a database of approximately 4000 facilities in seven OECD countries, empirical evidence is found for the role that both factors play in encouraging the adoption and certification of EMS's, but that the relative importance of different factors varies according to facility size.